WORK DISCIPLINE AFFECTED BY THE WORK ENVIRONMENT, ORGANIZATIONAL CULTURE AND LEADERSHIP IMPACT ON EMPLOYEE PERFORMANCE - Akhmad Nurrofi; Sri Sulistyaningsih; Martini Martini (LPPM STIE Anindyaguna, 2022)
This study is to analyze the influence of the work environment, organizational culture and leadership on work discipline that has an impact on employee performance in the organization In this study, researchers took as many as 35 respondents. Implementation of sampling using a census sampling technique as a whole sampling to respondents / employees Data analysis techniques using multiple regression. The results of the study have a positive and significant influence on work discipline, meaning that the better the work environment, the better the employee's work discipline. On the other hand, there is a positive and significant influence on organizational culture on work discipline, meaning that the better the organizational culture will increase work discipline, there is a positive and significant influence on work discipline, meaning that the better the leadership will increase work discipline. With the increased work discipline, it is expected that employee performance will increase in this study, work discipline has an effect on employee performance.